2018
DOI: 10.1159/000487103
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Campylobacter rectus</i></b> in the Oral Cavity Correlates with Proteinuria in Immunoglobulin A Nephropathy Patients

Abstract: Background: Periodontitis-related pathogens, such as Campylobacter or Treponema species, have recently been shown to be associated with immunoglobulin A nephropathy (IgAN). Some strains of Streptococcus mutans, a major pathogen of dental caries, harbour the cnm gene that encodes a collagen-binding protein (Cnm). This has also been demonstrated to be associated with urinary protein levels in IgAN patients. Objectives: The purpose of the present study was to analyse the association of IgAN with C. rectus, Trepon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…Recent findings have described an association between C. rectus abundance in the mouth and proteinuria among patients with IgA nephropathy . Although a reverse causality cannot be excluded, and results cannot be generalized to other proteinuric conditions, it is possible that C. rectus determines changes in the permselectivity properties of the glomerulus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have described an association between C. rectus abundance in the mouth and proteinuria among patients with IgA nephropathy . Although a reverse causality cannot be excluded, and results cannot be generalized to other proteinuric conditions, it is possible that C. rectus determines changes in the permselectivity properties of the glomerulus .…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have described an association between C. rectus abundance in the mouth and proteinuria among patients with IgA nephropathy. 29 Although a reverse causality cannot be excluded, and results cannot be generalized to other proteinuric conditions, it is possible that C. rectus determines changes in the permselectivity properties of the glomerulus. 30 When protein waste with urines is significant, increased sodium retention occurs by either hyperactivated renin-angiotensin-aldosterone system (RAAS) or impaired sodium handling and excretion, 31,32 with consequent development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…protein (Cnm) on their cell surface exhibit a binding ability for the extracellular matrix; thus, Cnm may be a virulence factor in several diseases such as infective endocarditis [12], aggravated cerebral haemorrhaging [13][14][15], non-alcoholic steatohepatitis [16], and inflammatory bowel disease [11]. Furthermore, the results of our recent studies suggest that Cnm-positive S. mutans strains are associated with IgAN [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…rectus with cnm -positive S . mutans in saliva was associated with high urinary protein levels in patients with immunoglobulin A nephropathy (IgAN) [ 32 ]. Microalbumin reflects endothelial dysfunction, and endothelial dysfunction is thought to play a role in the mechanisms leading to CSVD-related brain changes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some case reports have shown that there is an association between C. rectus and cavernous sinus thrombosis [30,31], no cohort study has investigated the association between C. rectus and neurological disease. However, Misaki et al have reported that the coexistence of C. rectus with cnm-positive S. mutans in saliva was associated with high urinary protein levels in patients with immunoglobulin A nephropathy (IgAN) [32]. Microalbumin reflects endothelial dysfunction, and endothelial dysfunction is thought to play a role in the mechanisms leading to CSVD-related brain changes [33].…”
Section: Plos Onementioning
confidence: 99%